2022
DOI: 10.1002/adfm.202204906
|View full text |Cite
|
Sign up to set email alerts
|

Sub 150 nm Nanoscale Gallium Based Metal–Organic Frameworks Armored Antibiotics as Super Penetrating Bombs for Eradicating Persistent Bacteria

Abstract: Persistent bacteria, such as intracellular and biofilm bacteria, are critical challenges in clinic treatment because they are refractory to antibiotics management under the shelter of cytomembrane and biofilm. Conventional strategies to combat intracellular bacteria are using high doses of antibiotics, which may bring the risk of drug resistance, and debridement of the biofilm increases patients' pain and economic burden. Currently, the use of antibiotics is irreplaceable and it is necessary to develop new str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Iron is required for bacterial survival, growth, proliferation, and pathogenesis, which participate in DNA synthesis and energy metabolism as a cofactor. According to our previous work, Ga-based compounds could remove S. aureus biofilm [ 26 ]. Therefore, we employed proteomics analysis to explore how Ga 3+ ions affected iron metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron is required for bacterial survival, growth, proliferation, and pathogenesis, which participate in DNA synthesis and energy metabolism as a cofactor. According to our previous work, Ga-based compounds could remove S. aureus biofilm [ 26 ]. Therefore, we employed proteomics analysis to explore how Ga 3+ ions affected iron metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Biofilm-associated infections and aseptic osteolysis due to the overactivation of osteoclasts are two key factors that limit the clinical application of titanium-based implants. Our previous results showed that Ga 3+ ions significantly inhibited biofilm formation and osteoclast differentiation, but the specific mechanism was unknown [ 20 , 26 ]. It will be of great clinical significance to prepare a Ti-Ga alloy to simultaneously solve the above two problems.…”
Section: Discussionmentioning
confidence: 99%
“…Bio lm-associated infections and aseptic osteolysis due to the overactivation of osteoclasts are two key factors that limit the clinical application of titanium-based implants. Our previous results showed that Ga 3+ ions signi cantly inhibited bio lm formation and osteoclast differentiation, but the speci c mechanism was unknown [20,23]. It will be of great clinical signi cance to prepare a Ti-Ga alloy to simultaneously solve the above two problems.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is required for bacterial survival, growth, proliferation, and pathogenesis, which participate in DNA synthesis and energy metabolism as a cofactor. According to our previous work, Ga-based compounds could remove S. aureus bio lm [23]. Therefore, we employed proteomics analysis to explore how Ga 3+ ions affected iron metabolism.…”
Section: S Aureus Iron Metabolism Disorder Following Ga Treatmentmentioning
confidence: 99%
“…Similarly, MOFs can sustainably release the stored metal ions and thus achieve a long-term antibacterial effect. 88 Xiaoxue Yao et al prepared omniphobic porous hydrogels loaded with zinc imidazolate framework 8 (ZIF–8) nanoparticles as wound dressings. 38 Anchoring of ZIF–8 nanoparticles endowed hydrogels with a reentrant architecture and increased roughness, which was beneficial for eliminating the adhesion of pathogens.…”
Section: Engineered Surfaces For Adhesion Inhibitionmentioning
confidence: 99%